Chemical ozone loss in the Arctic vortex in the winter 1995-96: HALOE measurements in conjunction with other observations - Müller, R.; Grooß, J. -U.; McKenna, D. S.; Crutzen, P. J.; Brühl, C.; Russell III, J. M.; Gordley, L. L.; Burrows, J. P.; Tuck, A. F. (Annales Geophysicae, 1999)
Severe chemical ozone loss has been detected in the Arctic in the winter and spring of 1995-96 by a variety of methods. Extreme reductions in column ozone due to halogen catalysed chemistry were derived from measurements of the Halogen Occultation Experiment (HALOE) on board the Upper Atmosphere Research Satellite in the Arctic vortex. Here, we discuss further aspects of the HALOE observations in the Arctic over this period. Potential problems, both in the data themselves and in the methodology of the data analysis are considered and the reason for the differences between the Arctic ozone losses deduced from HALOE data version 17 and 18 is analysed. Moreover, it is shown that HALOE measurements in the Arctic in winter and spring 1995-96 compare well with observations by other ground-based and satellite instruments. Key words. Chemical ozone loss (Arctic vortex 1995 · 96; halogen chemistry)